Estrategias didàcticas y el retraso escolar - Cajas Toctaguano, Gloria Alexandra (2016)
The research on the School Delay is a problem that affects the academic performance of freshmen Basic Education of the Education Unit Juan Abel Echeverria Parish of Latacunga Canton Eloy Alfaro Towr San Felipe. Town aim of the research was to diagnootic the causes of school retardation in children to improve their learning during the research process qualitative methodology and cuantitive that allowed us to collect adequate information for researchit was used, the survey was also used to it was applied to parents for see if they knew about the teaching strategies that the teacher uses in the classroom for children to have a better understanding of the issues, we apply a intervica to tcachers for rinow if they have a notion about what is school delay and strategies used to work with children who have difficulty learning and observation sheet was aimed at children to know their level of learning and how they operate in the activities they perform these instruments was very helpful to culminate with our proposed, for this reason objective is important to teaching strategies to help students improve their school performance. This also depends in teaching he take car and attention of parents towards their children so for paramis give thert childrens the motivsteal and teel desive to learn , the teacher must first know about that is the school for later take a plan.issueb or strategies hract to help attention a draw attention to the infant so that all students can meet he curricular objective get better he infant anowledge of all students,and and students completc be continue with their studies and become a furure professional.